2000
DOI: 10.1139/z99-236
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spatial stability of coyote (Canis latrans) home ranges in southeastern Colorado

Abstract: Long-term stability of territorial boundaries has not been well documented in canids. To evaluate the prevalence of long-term spatial stability of coyote (Canis latrans) home ranges, we compared the overlap of territorial boundaries and the spatial distribution of telemetry locations of packs in southeastern Colorado. From August 1983 to July 1988 (period l), 16 coyotes from six packs were radio-tracked. From April 1996 to August 1997 (period 2), 12 coyotes from six packs were captured and tracked in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
1
15
0
6
Order By: Relevance
“…Perhaps improved environmental conditions on the PCMS have elevated fox survival rates since the earlier swift fox research was conducted. Kitchen et al (2000) found significantly smaller coyote home ranges and higher lagomorph counts during fieldwork in the 1990s than were found during work conducted on the same site in the 1980s, indicating a higher prey base and coyote density. Changes in canid survival rates and density in relation to increasing prey biomass have been reported (Keith 1983;Fuller 1989;Knowlton et al 1999).…”
Section: Discussionmentioning
confidence: 55%
“…Perhaps improved environmental conditions on the PCMS have elevated fox survival rates since the earlier swift fox research was conducted. Kitchen et al (2000) found significantly smaller coyote home ranges and higher lagomorph counts during fieldwork in the 1990s than were found during work conducted on the same site in the 1980s, indicating a higher prey base and coyote density. Changes in canid survival rates and density in relation to increasing prey biomass have been reported (Keith 1983;Fuller 1989;Knowlton et al 1999).…”
Section: Discussionmentioning
confidence: 55%
“…Por ejemplo, en machos, la disminución o ausencia de individuos adultos quizá se deba a las presiones por encontrar y fecundar un mayor número de hembras para preservar sus genes. En contraste, las hembras se ven más interesadas en la búsqueda de alimento y refugios para garantizar el desarrollo de las crías (Bond & Wolf 1999, Jonsson et al 2000, Kitchen et al 2000. Esto se documentó en el área de estudio para Heteromys gaumeri .…”
Section: Discussionunclassified
“…A general consensus of studies indicates coyote space use can be stable through time (Kitchen et al 2000a;Young et al 2006), but varies by geographic location. In addition, home range size of resident packs can be influenced by resources or habitat types (Gese et al 1988a).…”
Section: Introductionmentioning
confidence: 99%